Vocal warm-up and cool-down in teachers: A quasi-experimental controlled study - Masson, Maria Lúcia Vaz; Fabbron, Eliana Maria Gradim [UNESP]; Loiola-Barreiro, Camila Miranda (FapUNIFESP (SciELO), 2019)
Purpose: To verify the effects of vocal warm-up (VWU) and vocal cool-down (VCD) strategies on teachers. Methods: A quasi-experimental exploratory blind-evaluator study with control group that included teachers from a public secondary school. Teachers assigned to the experimental group (EG) performed VW prior to classes and VCD after classes. Teachers in the control group (CG) did not perform VWU and simply got voice rest after classes. Intergroup (EG vs. CG) and intragroup (pre-test versus post-test) comparisons were drawn from an auditory-perceptual evaluation, acoustic analysis, and self-reported discomfort. The mean acoustic and discomfort indicators and the percentage of improvement or worsening of vocal quality were calculated with a statistically significance level of p<0.05. Results: EG and CG did not differ from each other in the intergroup analysis. The intragroup analysis showed that VWU improved voice quality and decreased the degree of body-related discomfort. VCD decreased both the fundamental frequency (f0) and the degree of discomfort, particularly in relation to the voice aspects. Vocal rest did not show any statistical difference. Conclusion: VWU showed positive effects on the auditory-perceptual evaluation and self-reported discomfort (body). VCD impacted f0 and self-reported discomfort (voice). Due to the exploratory nature of the research, the statistical power was not enough to demonstrate a difference in the comparison between EG and CG. However, the results indicate a potential for protecting teachers' voice and may be incorporated into daily work settings. Further controlled studies with random samples and greater numbers of participants should be conducted to confirm these results.
Keywords: Faculty; Occupational exposure; Occupational health; Protective factors; Voice; Voice training